Physicochemical and Sensory Quality of Meat in Commercial Native Chicken, Backyard Native Chicken, Commercial Broiler and Spent Layer Chicken: 10.5958/2581-6616.2020.00007.9 - kumar, Sathish; Kulkarni, V. V. (Journal of Meat Science, 2021)
A study was planned on the physicochemical and sensory quality of meat in commercial native chicken (CNC), backyard native chicken (BNC), commercial broiler (CB) and spent layer chicken (SLC) on 12 birds of either sex in each class. Birds slaughtered by Jatka meth od and physico-chemical parameters (pH, Water Holding Capacity, Extract Release Volume, Muscle fibre diameter, sarcomere length, collagen content, R-Value, shear force value and sensory score) were recorded in breast and leg meat, separately. Nuggets were prepared to assess the sensory quality. Water Holding Capacity (WHC) was significantly higher (P<0.01) and muscle fiber diameter and collagen content were significantly lower (P<0.01) in CB than BNC and SLC. Shear force values for fresh and cooked meat were significantly lower in CB and highest in SLC. The collagen content was significantly higher in males than females and in thigh meat than breast meat. The chewability in the cooked thigh meat was better than breast meat. The overall acceptability of nugget for CB was significantly higher (P<0.01) than CNC, BNC and SLC. The study revealed that CB meat quality was better than CNC, BNC and SLC in overall physicochemical and sensory quality in terms of low collagen content and higher tenderness, water holding capacity, juiciness and overall acceptability.